Методика виготовлення стереолітографічної моделі щелеп при проведенні субперіостальної імплантації - Чертов, Сергій Олександрович; Chertov, S. O. (My University, 2015)
Автором статті запропонований спосіб виготовлення стереолітографічної моделі щелеп при проведенні одноетапної субперіостальної імплантації, на що отримано Патент України на корисну модель № 22810 від 25.04.07. Установлено, що комп'ютерне дослідження на томографі з програмним забезпеченням «Dento Scan» і спіральним скануванням зображення дає можливість отримати зрізи кісткової тканини щелепи у визначеній ділянці досліджуваного альвеолярного відростка. За допомогою програмного забезпечення «SimPlant Pro module Import (Materialise NV)» отримали побудову тримірної просторової моделі щелепи і за технологією пошарового виготовлення тримірних об'єктів із рідких полімерних композицій, затвердіння яких проводиться лазерним опроміненням, виготовили стереолітографічну модель. Запропонована методика забезпечує виконання субперіостальної імплантації за один хірургічний етап за рахунок комплексного використання даних спірального томографічного дослідження, комп'ютерного просторового моделювання щелепи і лазерної стереолітографії. The author proposed a way of getting a stereolithographic model of jaws during the one-step subperiosteal implantation; we got a patent of Ukraine for an utility model (no. 22810, Date of filing 25.04.07). We had been examining the state of the bone tissue and the soft tissue attachments in the edentulous area using the computed tomography with Dento Scan software package to investigate the bone tissue sections of the in the area of alveolar ridge and by the spiral scanning. Using SimPlant Pro module Import (Materialise NV) software package, we received a threedimensional spatial model of the jaw and with the layer-by-layer manufacturing of three-dimensional objects from liquid polymer compositions, hardening of which is held by a laser irradiation, then made a stereolithographic design model that allowed us producing and attaching the titanium implant. The titanium implant was manufactured by the stereolithographic model, using the standard technology: making a copy of a stereolithographic model from plaster and refractory masses for titanium casting; designing and manufacturing of framework of subperiosteal implant on a plaster copy of stereolithographic model; testing the framework of subperiosteal implant on the stereolithographic model copy made of refractory mass; vacuum casting of titanium; X-ray casting control; final casting processing; casting control of implants on the stereolithographic models; sandblasting and acid etching of residual contamination; implant processing in the physiological salt solution and closedloop autoclave sterilization; installing the subperiosteal design on the implant site of a patient. We established that the computed tomography with Dento Scan software package and spiral scanning allows to get bone tissue sections of the jaw in a specific area of the investigated alveolar ridge. Using SimPlant Pro module Import (Materialise NV) software package, we got a threedimensional spatial model of the jaw and with the layer-by-layer manufacturing of three-dimensional objects from liquid polymer compositions, hardening of which is held by a laser irradiation, we made a stereolithographic model. The proposed method ensures the implementation of subperiosteal implantation in one surgery stage by using the comprehensive data of spiral tomographic study, computed spatial modeling of the jaw and the laser stereolithography.
Method for obtaining the stereolithographic model of jaws during the one-step subperiosteal implantation
Keywords: субперіостальна імплантація; спіральна томографія; лазерна стереолітографія; subperiosteal implantation; spiral tomography; laser stereolithography